Assessment of Depression and Social Support among Women with Breast Cancer in Kerbala City, Iraq 2022 - Rusul Fahim Obaid; Shahrazad S. AL Jubori; Ahmed Mahdi Hasan Al Tameemi (Karbala Journal of Medicine, 2025)
Background: Breast cancer is the most frequent malignancy among females worldwide. It is associated with more severe mental and emotional outcomes than other cancers. Depression is one of the psychological consequences of breast cancer. The prevalence of depression is influenced by multiple factors, one of which is the level of social support. This study aimed to assess the degree of depression and social support among breast cancer women, the relationship they have with each other, and their association with socio-demographic characteristics. Methods: A cross-sectional study involved 250 women with breast cancer who attended the oncology clinics of two hospitals in Kerbala City from January to June 2022. Data were collected by direct interview using a structured questionnaire. Patient Health Questionnaire-9 was used to diagnose and assess the level of depression. A multidimensional scale of perceived social support was applied to assess the patient’s social support. Results: Depression was recorded in 36.8% of patients. About 54% of breast cancer women had high total social support. The result showed that depression decreases significantly with the increase in the total social support in breast cancer women. Conclusions: Depression is experienced by more than one-third of women with breast cancer. It decreases significantly with the increase in social support for them. Integration of screening programs for depression and psychosocial service provision in routine cancer care is recommended. Coordinating different types of support from the family, healthcare professionals, or community organizations is necessary when they work together. Financially and psychologically support also demands. Keywords: Breast cancer, depression, social support.